A Proposed Model of Water-Retaining Walls in Tawiran Obando Bulacan: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The retaining walls consist mainly of a retaining wall and backfill soil. The engineering essence of a retaining wall is to keep retained soil in a certain shape and prevent it from falling (stability); however, a citizen around the area should have their consent first. We want to launch this study to help people living in that certain place lessen the problems they face every time a storm approaches or the water level rises. The research design used for the study was quantitative experimental research while utilizing purposive and simple random techniques. The statistical treatment used for this study was a T-test to determine the difference between the two groups of respondents. Using the questionnaire as the research instrument, the researchers surveyed to identify the level of acceptability of the model in terms of construction materials, structural designs, and procedures for waterways. The study's respondents are five professional civil engineers and five architects. The following procedures were undertaken in the process of developing the model: Preparing the materials needed, cutting the popsicle sticks, sticking them together with stick glue to make a house on an illustration board, placing the four (4) houses that have been made, for an illustration board, then cement on each side, construct the retaining wall behind the houses, The proposed Drain tunnel can now present. The results of the study in terms of the construction materials, designs and procedures, and mechanism to waterways for overflowing waters from drainage are strongly acceptable. The acquired overall mean of the Professional Civil Engineers was 3.63, interpreted as Strongly Acceptable. Professional Architects were 3.50, interpreted as Strongly Acceptable. It indicates no significant difference between the assessments of the two groups of respondents. To further improve the project, the respondents suggested adding a pumping station to help stop the water if the retaining wall can no longer handle the river's water level.
Keywords: Model; Retaining Walls; Tawiran Obando Bulacan